PEMANFAATAN APLIKASI DIGITAL DALAM PEMBELAJARAN BAHASA - Ruhaliah, Ruhaliah; Solehudin, Oleh; Isnendes, Retty; Hernawan, Hernawan; Sutisna, Ade; Hendrayana, Dian (Dimasatra, 2021)
The existence of a pandemic since March 2020 has caused teachers to be creative so that the teaching-learning process continues but does not become a heavy burden for all parties. To overcome this, various activities are carried out online. But this activity sometimes causes burnout. On the positive side, it creates creativity so that various activities can continue, including in the fields of education and teaching. The purpose of this paper is to explain various digital applications that can be used in language learning, both related to the four language skills and in general, which can be utilized in blended learning or hybrid learning activities. The method used is descriptive. The result is a grouping of learning applications that can be used based on four language skills. But there are also applications that can be used without these classifications.